Investment Feasibility of the Teluk Gelam Tourism Area in Ogan Komering Ilir Regency - Sadewo, Rifki Ari; Sartika, Dewi (Moneta : Journal of Economics and Finance, 2025)
This study analyzes the financial feasibility and development strategy for the Teluk Gelam Lake Tourism Area in Ogan Komering Ilir Regency (OKI). Financial feasibility is assessed using Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Benefit-Cost Ratio (BCR). A mixed-method approach was applied, involving questionnaires distributed to 450 respondents across 18 sub-districts and interviews with key stakeholders. The financial indicators show the project is feasible: NPV IDR 27.6 billion, IRR 5.94%, BCR 1.19, and a payback period of 10 years. While financially viable, the low IRR and lengthy payback period highlight the need for strategies to boost revenue and tourism appeal. Recommendations include providing investment incentives, improving accessibility, enhancing facilities, and applying an ecotourism framework. With proper planning and collaboration among stakeholders, Teluk Gelam Lake has strong potential to become a leading sustainable tourism destination.